2005
DOI: 10.1073/pnas.0504750102
|View full text |Cite
|
Sign up to set email alerts
|

Osteo-chondroprogenitor cells are derived from Sox9 expressing precursors

Abstract: The transcription factor Sox9 is expressed in all chondroprogenitors and has an essential role in chondrogenesis. Sox9 is also expressed in other tissues, including central nervous system, neural crest, intestine, pancreas, testis, and endocardial cushions, and plays a crucial role in cell proliferation and differentiation in several of these tissues. To determine the cell fate of Sox9-expressing cells during mouse embryogenesis, we generated mice in which a Cre recombinase gene preceded by an internal ribosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
479
0
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 527 publications
(502 citation statements)
references
References 27 publications
19
479
0
4
Order By: Relevance
“…This role is similar to its function in the hair bulge, intestinal epithelium, and neural crest (Cheung and Briscoe, 2003;Blache et al, 2004;Vidal et al, 2005). Sox9 expression is first detected at $E10.5 in the early pancreatic MPC, and lineage tracing revealed that the ''first-wave'' Sox9 þ progenitors, like Pdx1 þ and Ptf1a þ progenitors, produce cells of all three pancreatic lineages (Akiyama et al, 2005). Sox9 expression persists in the endocrine/duct bipotent progenitor pool located in the central epithelial cords of the maturing epithelial arbor during the secondary transition (Seymour et al, 2007;Lynn et al, 2007).…”
Section: Sox9mentioning
confidence: 74%
“…This role is similar to its function in the hair bulge, intestinal epithelium, and neural crest (Cheung and Briscoe, 2003;Blache et al, 2004;Vidal et al, 2005). Sox9 expression is first detected at $E10.5 in the early pancreatic MPC, and lineage tracing revealed that the ''first-wave'' Sox9 þ progenitors, like Pdx1 þ and Ptf1a þ progenitors, produce cells of all three pancreatic lineages (Akiyama et al, 2005). Sox9 expression persists in the endocrine/duct bipotent progenitor pool located in the central epithelial cords of the maturing epithelial arbor during the secondary transition (Seymour et al, 2007;Lynn et al, 2007).…”
Section: Sox9mentioning
confidence: 74%
“…In the skeleton, SOX9 expression precedes RUNX2, and subsequently, SOX9 expression is maintained during the whole process of bone formation, from chondrocytes to osteoblasts. (47) The coordination between SOX9 and RUNX2 is highly important for the determination of MSC fate. It has been shown previously that SOX9 is able to exert a dominant inhibitory effect on RUNX2 function (32) ; however, the precise mechanisms involved are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This process requires the initial specification of precartilaginous cells (chondroprogenitors), which are not yet fully committed toward the cartilage lineage, and the following determination of a subset of these cells to form the definite cartilaginous condensation (Akiyama et al, 2005). The limb mesenchyme appears to have an intrinsic chondrogenic potential as a default fate, as can be seen in mesenchymal micromass cultures (see e.g., DeLise et al, 2000).…”
Section: Condensation Of the Digit Anlagenmentioning
confidence: 99%
“…Sox9 directly regulates the expression of Col2a1 (Lefebvre et al, 1997;Ng et al, 1997). However, the expression of Sox9 alone is not sufficient for definitive determination of the chondrogenic cell fate, because cells expressing Sox9 in vivo can still adopt other cell fates (Akiyama et al, 2005). Heterozygous mutations in SOX9 cause campomelic dysplasia, a generalized lethal chondrodysplasia with sex reversal (Wagner et al, 1994).…”
Section: Condensation Of the Digit Anlagenmentioning
confidence: 99%